OPTIMALISASI GREENHOUSE SEKOLAH SEBAGAI LABORATORIUM HIDUP BERBASIS QR CODE SMP NEGERI 10 SALATIGA - Ulya, Septi Asma; Zarin, Khofifah Ike Umi; Azizah, Isnaeni Waffiq; Ilham, A.Reza Fais; Malihah, Noor (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This community service activity aims to optimize the school's greenhouse as a digital Living Laboratory based on QR Code technology at SMP Negeri 10 Salatiga. The effort was motivated by a significant gap between the ideal potential of the greenhouse as a living laboratory for Science education and its current condition, which is poorly maintained, lacks plant identification, and is dominated by conventional teaching methods. The service focused on the problem of transforming the physical asset of the greenhouse into an interactive digital learning resource. The implementation method employed was Action-based Implementation, structured into four main stages: needs analysis, development of QR Code-based digital content, physical revitalization of the greenhouse, and installation of the QR Code system. The implementation results show successful physical transformation, marked by a clean and structured greenhouse environment (98.0% of students agree), and successful implementation of the digital system with the installation of 35 big data-integrated QR Codes. The main conclusion indicates that this innovation received very positive acceptance from students (an average of over 85%), particularly in the aspects of information access convenience (96.7%) and increased motivation in learning Science (90.0%). Thus, the integration of QR Code technology proves effective as an innovative solution for providing contextual and responsive Science learning media. Future development prospects can focus on the integration of gamification and the development of an integrated monitoring system for the evaluation of students' self-directed learning. ABSTRAK Kegiatan pengabdian ini bertujuan untuk mengoptimalkan greenhouse sebagai Laboratorium Hidup digital berbasis QR Code di SMP Negeri 10 Salatiga dilatarbelakangi oleh adanya kesenjangan potensi ideal greenhouse sebagai laboratorium hidup dalam pembelajaran IPA dan kondisi yang kurang terawat, minim identitas, serta didominasi oleh metode pengajaran konvensional. Dalam pengabdian berfokus pada masalah mengubah aset fisik greenhouse menjadi sumber belajar digital interaktif. Metode pelaksanaan yang digunakan adalah Pengembangan dan Implementasi Berbasis Aksi (Action-based Implementation) melalui empat tahapan utama: analisis kebutuhan, pengembangan konten digital berbasis QR Code, Revitalisasi fisik greenhouse, dan instalasi sistem QR Code. Hasil pelaksanaan menunjukkan keberhasilan transformasi fisik, yang ditandai dengan lingkungan greenhouse yang bersih dan terstruktur (98,0% siswa setuju), serta keberhasilan implementasi sistem digital dengan pemasangan 35 QR Code terintegrasi big data. Simpulan utama menunjukkan bahwa inovasi ini memiliki penerimaan yang sangat positif dari siswa (rata-rata di atas 85%), terutama dalam aspek kemudahan akses informasi (96,7%) dan peningkatan motivasi belajar IPA (90,0%). Dengan demikian, integrasi teknologi QR Code terbukti efektif sebagai solusi inovatif untuk menyediakan media pembelajaran IPA yang kontekstual, dan responsif. Prospek pengembangan ke depan dapat difokuskan pada integrasi gamifikasi dan pengembangan sistem monitoring terpadu untuk evaluasi belajar mandiri siswa.